PENGARUH MASSAGE EFFLEURAGE DAN FRICTION TERHADAP FLEKSIBILITAS OTOT PUNGGUNG BAWAH PADA BOLA VOLI - Aditya Lutfi Setyawan; Sri Sumartiningsih (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA (UTP), 2026)
This study aims to determine the effect of effleurage and friction massage on increasing the flexibility of the lower back muscles in volleyball UKM at Semarang State University. This study uses a type of quantitative research with experimental methods using Quasi Experimental Design and using the equivalent design of Pretest Posttest With Control Group Design. The population in this study was 50 people and the sample taken using random sampling was 30 people. This research instrument uses a sit and reach box. The intervention provided is a combination of effleurage and friction massage with 1 session and 10 minutes of treatment per person. The results showed that the application of effleurage and friction massage can significantly improve the flexibility of the lower back muscles. The significance values are p = 0.001 and p = 0.095 less than 0.05 (p<0.05), and the experimental group experienced an increase of 9%, while the control group experienced an increase of 3%. The results in this study prove that there is an increase in flexibility of the lower back muscles that allows to improve performance and reduce the risk factor of injury to athletes.